Preparation of Bioethanol from Pineapple Peel (ananas comosus L. Mer) Waste with the Addition of Hydrochloric Acid and Citric Acid Catalysts - Nur Khairani; Rizka Mulyawan; Meriatna; Agam Muarif; Syamsul Bahri; Iqbal Kamar (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2024)
Bioethanol is ethanol derived from biological sources. Bioethanol can be produced from plants that contain many starch and cellulose compounds using the help of yeast activity. One of them is pineapple peel which can add a variety of basic materials for bioethanol production which is economical and easy to obtain. This study aims to analyze the effect of acid hydrolysis on glucose content, analyze the effect of fermentation time and the effect of yeast weight on bioethanol characteristics. This research has been done before and only focused on one catalyst. What has never been done is comparing the two catalysts. The research was conducted using hydrolysis fermentation and distillation using hydrochloric acid and citric acid catalysts with yeast weight variation of 12, 15, and 17 grams, fermentation time variation of 2, 3, 4, and 5 days. In this research, glucose test, density analysis, yield analysis, and GC-MS were conducted. The results of this study showed that the best results in the treatment of hydrochloric acid catalyst at a yeast weight of 15 grams, and obtained glucose levels of 6.90% for hydrochloric acid and 5.10% for citric acid, density test obtained the highest results at a yeast weight of 15 grams 4 days 0.8288 gr / ml for hydrochloric acid catalyst and the lowest density obtained at a yeast weight of 17 grams 5 days 0, 8168 gr/ml, yield analysis obtained at the amount of 15 grams of yeast with a fermentation time of 14 days of 4.3536% in the treatment of hydrochloric acid catalyst and 3.8557% in the treatment of citric acid catalyst fermentation time of 3 days, GC-MS test showed that ethanol contained in the test sample.